A Multi Criteria Decision Tool for Fixed Platform Decommissioning Using Analytic Hierarchy Process (AHP) - QAID ALGHURIBI, TAREQ MOQBEL (2018)
The oil and gas cycle runs from field exploration, development, production to decommissioning and abandonment, when a field becomes unprofitable for production.